Taiwan dermatological association recommendations for coronavirus disease of 2019 vaccination in patients treated with immunotherapeutics - Chih-Hung Lee; Yu-Huei Huang; Chia-Yu Chu (Dermatologica Sinica, 2021)
This article aims to present current COVID-19 vaccination considerations for patients on immunotherapeutics for the management of immune-mediated dermatological diseases and summarize the recommendations relevant to clinical practice in Taiwan. These Taiwan Dermatological Association (TDA) recommendations are intended to be dynamic in nature and serve as an interim guide to optimize patient care at this current juncture. It is expected that our clinical practice would continually evolve and be informed by new evidence that emerges in this pandemic.